The Combination of Text Classifiers Using Reliability Indicators - Bennett, Paul; Dumais, Susan; Horvitz, Eric (Informtion Retrieval (This paper revises and extends work originally presented in [Bennett, Dumais, & Horvitz; SIGIR 2002].), 2005)
The intuition that different text classifiers behave in qualitatively different ways has long motivated attempts to build a better metaclassifier via some combination of classifiers. We introduce a probabilistic method for combining classifiers that considers the context-sensitive reliabilities of contributing classifiers. The method harnesses reliability indicators–variables that provide signals about the performance of classifiers in different situations. We provide background, present procedures for building metaclassifiers that take into consideration both reliability indicators and classifier outputs, and review a set of comparative studies undertaken to evaluate the methodology.